2010
DOI: 10.1002/humu.21159
|View full text |Cite
|
Sign up to set email alerts
|

Assessing individual interethnic admixture and population substructure using a 48-insertion-deletion (INSEL) ancestry-informative marker (AIM) panel

Abstract: Estimating the proportions of different ancestries in admixed populations is very important in population genetics studies, and it is particularly important for detecting population substructure effects in case-control association studies. In this work, a set of 48 ancestry-informative insertion-deletion polymorphisms (INDELs) were selected with the goal of efficiently measuring the proportions of three different ancestries (sub-Saharan African, European, and Native American) in mixed populations. All selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
281
0
13

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(313 citation statements)
references
References 41 publications
19
281
0
13
Order By: Relevance
“…Individual interethnic admixtures were determined using a panel of 48-INDELs ancestry-informative-marker (AIM) panel, previously applied for Brazilian population analysis. Genotyping of the 48 INDEL markers in this study followed the methodology described by Santos et al (2010). This approach permitted estimates of individual and global admixture relative to three ancestry groups: European, African Sub-Saharan and Amerindian.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual interethnic admixtures were determined using a panel of 48-INDELs ancestry-informative-marker (AIM) panel, previously applied for Brazilian population analysis. Genotyping of the 48 INDEL markers in this study followed the methodology described by Santos et al (2010). This approach permitted estimates of individual and global admixture relative to three ancestry groups: European, African Sub-Saharan and Amerindian.…”
Section: Methodsmentioning
confidence: 99%
“…A set of 48 ancestry-informative insertiondeletion polymorphisms (INDELs) was developed aiming at measuring the proportions of three different ancestries, sub-Saharan African, European, and Amerindian, in mixed populations (Santos et al 2010). This panel allowed accurate estimation of individual and global interethnic admixture relative to the ancestry of Brazilians from three regions of the country.…”
Section: Introductionmentioning
confidence: 99%
“…Kosoy et al (2009) have shown that panels of 24 AIMs are useful to ascertain the origin of subjects from particular continents and to correct for population stratification at the population level. Some low-medium cost multiplex panels of AIMs have been published (Lins et al, 2010;Santos et al, 2010); however, these may vary in their informativeness. Therefore, the best option for an investigator performing an admixture study is to assess which combination of AIMs is most informative for the target population.…”
Section: Introductionmentioning
confidence: 99%
“…3 Moura et al refer to results from populations in Columbia, Peru and Puerto Rico as 'the literature' for American populations, but this ignores studies performed in Brazil itself, to which our results are more similar. [4][5][6] The one Brazilian study cited was that of Pena et al 7 We noted in our text that, in contrast to our own sample, this paper uses a sample unlikely to be representative of Ceará state or Fortaleza and includes no pseudoancestors of any kind. This is known to distort ancestry in admixed populations.…”
mentioning
confidence: 89%